Strength Improvement of Ferritic/Martensitic T91 Steel by Cross Wedge Rolling at Different Austenitizing Temperatures - He, T.; Min, L.; Liu, H.J. (Проблемы прочности, 2017)
Cross wedge rolling (CWR) is a forming technique wherein the processed material microstructure is controlled by the processing temperature. The initial results on CWR-processed T91 steels at different austenitizing temperatures are discussed with the microstructure analysis by various characterization techniques, such as the optical and scanning electron microscopies. The processed T91 specimens were much harder than water-quenched ones, their hardness being independent of the ausforming temperatures despite their microstructural differences.